Effect of dapagliflozin on the structural and functional properties of arterial vessels in patients with type 2 diabetes mellitus in combination with obesity - О. А. Soloviuk; R. L. Kulynych (Patologìâ)
Modern trends in the treatment of type 2 diabetes mellitus (DM) should include not only the normalization of carbohydrate metabolism disorders, but also a possible positive effect on the cardiovascular system. The use of the drug dapagliflozin for several years has proven to reduce the manifestations of heart failure. However, the possible significance of dapagliflozin in the reversal of structural and functional changes in the arteries in patients with type 2 DM and obesity has not been studied enough.